2013
DOI: 10.7314/apjcp.2013.14.3.1715
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Differential Distribution of Microvessel Density, Possibly Regulated by miR-374a, on Breast Cancer Prognosis

Abstract: Background: The discovery that microRNAs (miRNAs) regulate proliferation, invasion and metastasis provides a principal molecular basis of tumor heterogeneity. Microvessel distribution is an important characteristic of solid tumors, with significant hypoxia occurring in the center of tumors with low blood flow. The distribution of miR-374a in breast tumors was examined as a factor likely to be important in breast cancer progression. Methods: Breast tissue samples from 40 patients with breast cancer were classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
0
16
1
Order By: Relevance
“…We did not identify the relation of MVD with other clinical characteristics of BC. These results contradict the data of other authors that found an association of MVD with clinical characteristics and prognosis of BC (Li et al 2006 ; Popiela et al 2008 ; Fernández-Guinea et al 2013 ; Li et al 2013 ). We believe that the reason for these contradictions are due to the fact that in contrast to the above-mentioned authors in calculating of MVD we took into account only the normal microvessels, while the prognosis was associated with other types of tumor vessels.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…We did not identify the relation of MVD with other clinical characteristics of BC. These results contradict the data of other authors that found an association of MVD with clinical characteristics and prognosis of BC (Li et al 2006 ; Popiela et al 2008 ; Fernández-Guinea et al 2013 ; Li et al 2013 ). We believe that the reason for these contradictions are due to the fact that in contrast to the above-mentioned authors in calculating of MVD we took into account only the normal microvessels, while the prognosis was associated with other types of tumor vessels.…”
Section: Discussioncontrasting
confidence: 95%
“…However, its role in the progression of BC has been studied insufficiently and the received data are contradictory (Uzzan et al 2004 ). For example, several studies have indicated that a high microvessel density (MVD) in tumor is associated with more advanced stages and poor prognosis of BC (Popiela et al 2008 ; Fernández-Guinea et al 2013 ; Li et al 2013 ). At the same time, the other authors have found no association of MVD with clinical characteristics and long-term results of BC treatment (Fridman et al 2000 ; Gasparini 2001 ; Mohammed et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently dysregulated miRNAs have been reported that associated with every aspect of breast tumor biology, including tumor progression (Li et al, 2013a), apoptosis (Anaya-Ruiz et al, 2013), different distribution in clinicopathological subtypes (Li et al, 2013b), and acquisition of resistance to various chemotherapeutic agents. Causes of anti-cancer drug resistance are believed to be complex and current studies have indicated that the acquisition of chemotherapy drug resistance may also be modulated via the changes in miRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] It is likely that miR-374a serves a complex role in carcinogenesis that is context dependent.…”
Section: Disscussionmentioning
confidence: 99%
“…In highly invasive and metastatic tumors, it was lower at the edges than that in the center, and lower in cancer tissues than in normal tissues. 11 Taken together, the functions and molecular basis of miR-374a are complex and contradictory, thus more studies are needed to confirm its context-specific role.…”
Section: Introductionmentioning
confidence: 98%